1997
DOI: 10.1017/s0022029996001914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and time on the quantity of readily available water within fresh cheese curd

Abstract: Some of the textural changes that occur early in cheese maturation may be related to the redistribution of water within the cheese matrix. To examine this, a model cheese curd system was devised and explored. Initially, cheese curd was prepared using starter and chymosin and the curd pH was controlled by varying the draining and salting pH values. The quantity of serum that could be centrifuged from the resultant curd was less for lower pH curd and decreased in volume with time. The curd pH decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…4). Ramkumar et al [39] observed that the amount of whey centrifuged from a model Cheddar cheese decreased with increase in pH of the curd, suggesting that the capacity of the curd to physically retain water molecules, like the casein-moisture interactions in the cheese, were pH-sensitive. Kindstedt et al [23], working with Mozzarella cheese, also reported that the pH strongly affected the protein-moisture interactions and consequently the melting of the cheese, the cheeses losing their melting capacity at pH values below 5.0.…”
Section: Evolution Of the Melting Capacity Of The Cheesesmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Ramkumar et al [39] observed that the amount of whey centrifuged from a model Cheddar cheese decreased with increase in pH of the curd, suggesting that the capacity of the curd to physically retain water molecules, like the casein-moisture interactions in the cheese, were pH-sensitive. Kindstedt et al [23], working with Mozzarella cheese, also reported that the pH strongly affected the protein-moisture interactions and consequently the melting of the cheese, the cheeses losing their melting capacity at pH values below 5.0.…”
Section: Evolution Of the Melting Capacity Of The Cheesesmentioning
confidence: 99%
“…During storage, a decrease in expressible water of the cheese usually occurs (water whose mobility is not impeded by the macro-structure of the protein matrix and which can be expressed by centrifugation), such water being found together with the fat and the starter organisms in vacuoles and elongated pockets [33,39]. According to McMahon et al [33], after salting of the cheese, reorganization of the protein matrix possibly occurs, with subsequent absorption of water by these vacuoles/pockets during refrigerated storage.…”
Section: Evolution Of the Melting Capacity Of The Cheesesmentioning
confidence: 99%
“…Hardness decreased significantly (P < 0.001) with the progress of manipulation showing less solid-like behaviour as described by Ramkumar et al (1997). The highest firmness was observed in cheese made with curd without manipulation, while at the end of the third minute, the curd was very soft and the resulting cheese also showed the lowest hardness.…”
Section: Effects On Texturementioning
confidence: 70%
“…Results of TPA parameters of cheese are shown in Table 2. Hardness decreased significantly ( P < 0.001) with the progress of manipulation showing less solid‐like behaviour as described by Ramkumar et al. (1997).…”
Section: Resultsmentioning
confidence: 88%
“…Similar results were observed for several other cheese varieties, such as mozzarella (Guo et al . 1997; Ramkumar et al . 1997; Kindstedt and Guo 1998; Paulson et al .…”
Section: Discussionmentioning
confidence: 99%